Doing Research in Times of Crisis. An Auto/biography - Aneta Ostaszewska (Autobiografia)
The purpose of this paper is to examine the process of struggling with thoughts, emotions and experiences that emerged in the course of and as a result of my research during the Covid-19 pandemic. By referring to Liz Stanley’s notion of “auto/biography,” I strive to explore the meanings and implications of researching a researcher’s autobiography. I am interested in the epistemic discussion on the interrelationship of what is personal, political and/or institutional in the context of feminist studies. My aim is to reflect on such issues as the effect of research on the trajectory of my own auto/biography.